Biochemical evidence of translational infidelity and decreased peptidyltransferase activity by a sarcin/ricin domain mutation of yeast 25S rRNA - Panopoulos, Panagiotis (Nucleic Acids Res, 2004)
A C→U mutation (rdn5) in the conserved sarcin/ricin domain of yeast 25S rRNA has been shown to cause translational suppression and paromomycin resistance. It also separates the killing from the misreading effect of this antibiotic. We confirm these findings and provide in vitro evidence that rdn5 causes a 3-fold increase in translational errors and resistance to paromomycin. The role of this 25S rRNA domain in ribosome's decoding function was further demonstrated when 60S subunits from rdn5 cells were combined with 40S subunits from cells carrying an error-prone mutation in the eukaryotic accuracy center ribosomal protein S23, an homologue of Escherichia coli S12. These hybrids exhibited an error frequency similar to that of rdn5 alone, despite the error-prone mutation in S23. This was accompanied by extreme resistance to paromomycin, unlike the effects of the individual mutations. Furthermore, rdn5 lowers peptidyltransferase activity measured as a second-order rate constant (k(cat)/K(s)) corresponding to the rate of peptide bond formation. This mutation was also found to affect translocation. Elongation factor 2 (EF2)-dependent translocation of Ac-Phe-tRNA from the A- to P-site was achieved at an EF2 concentration 3.5 times lower than in wild type. In conclusion, the sarcin/ricin domain of 25S rRNA influences decoding, peptide bond formation and translocation.